2021
DOI: 10.3389/fmicb.2021.656306
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis of Antibiotic-Resistant Staphylococcus epidermidis Isolates From Clinical Sources in the Kwazulu-Natal Province, South Africa

Abstract: Staphylococcus epidermidis has become an important nosocomial pathogen. Multidrug resistance makes S. epidermidis infections difficult to treat. The study aims to describe the genomic characteristics of methicillin-resistant S. epidermidis (MRSE) isolated from clinical sources, to comprehend the genetic basis of antibiotic resistance, virulence, and potential pathogenicity. Sixteen MRSE underwent whole-genome sequencing, and bioinformatics analyses were carried out to ascertain their resistome, virulome, mobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…The sequence variations observed in these plasmids were either in the non-coding sequences or the ermC upstream regulatory sequence, which will be discussed in a later section on antimicrobial resistance. The RepL plasmids appeared to have a reasonably broad host range among the Firmicutes [ 43 ] as they have been observed with a high prevalence in S. epidermidis [ 54 ] but with a much lower prevalence among Enterococcus faecalis [ 55 ]. These plasmids lack mobilization genes but a lateral transfer of these ermC small RepL plasmids between staphylococci and bacteria from different genera had been previously demonstrated.…”
Section: Resultsmentioning
confidence: 99%
“…The sequence variations observed in these plasmids were either in the non-coding sequences or the ermC upstream regulatory sequence, which will be discussed in a later section on antimicrobial resistance. The RepL plasmids appeared to have a reasonably broad host range among the Firmicutes [ 43 ] as they have been observed with a high prevalence in S. epidermidis [ 54 ] but with a much lower prevalence among Enterococcus faecalis [ 55 ]. These plasmids lack mobilization genes but a lateral transfer of these ermC small RepL plasmids between staphylococci and bacteria from different genera had been previously demonstrated.…”
Section: Resultsmentioning
confidence: 99%
“…The pan-genome analysis of the isolates revealed the presence of phenol-soluble modulin (PSM) genes in isolate 9SE; the PSM genes have recently been identified as significant virulence factors, most notably in aggressive strains of S. aureus [ 37 ]. The presence of the IS256 and ica genes was used as a measure of the pathogenicity of S. epidermidis [ 38 ]. The 9SE strain possessed genes associated with biofilm formation ( icaA , icaB, icaC, and icaD ), IS256, and the gene regulator ( icaR ); biofilm-forming isolates have more capacity to adhere to medical devices, thus increasing the risk of device-associated infections [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although strains 14SP and 30SP lack the IS256 and ica genes, they were positive for other adhesins such as autolysin ( atl ), cell-wall-associated fibronectin-binding protein ( ebh ), elastin-binding protein ( ebp ), and Ser–Asp-rich fibrinogen-binding proteins ( sdrG ). Similarly, they were positive for other virulence factors, including cysteine protease ( sspB ), lipases ( geh and lip ), serine V8 protease ( sspA ), thermonuclease ( nuc ), and beta-hemolysin ( hlb ), which could increase their pathogenicity and differentiate them from the commensal strains [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in Ghana in 2018 reported high levels of antibiotic resistance among clinical isolates, particularly for commonly prescribed antibiotics such as amoxicillin and cipro oxacin 10 Therefore, this proposed cross-sectional study aims to assess the level of knowledge of antibiotic use and antibiotic resistance among nal year university students reading Bsc.…”
Section: Introductionmentioning
confidence: 99%